Choice Goal Attainment and Decision and Consumption Satisfaction - Heitmann, Mark; Lehmann, Donald R.; Herrmann, Andreas (Journal of Marketing Research, 2007)
Several individual, social-setting, and choice-set factors have been shown to be related to satisfaction. This article argues that these factors operate through a set of choice goals. Using panel data on purchasers of consumer electronics, the authors examine how five goals (justifiability, confidence, anticipated regret, evaluation costs, and final negative affect) drive decision and consumption satisfaction, which in turn determine loyalty, product recommendations, and the amount and valence of word of mouth.